Top-Oil Thermal Model for Power Transformers that Reflects Ambient Temperature Profile in Malaysia - Azman S.N.A.B.; Nik Ali N.H.; Doolgindachbaporn A.; Ariffin A.M.; Azis N.; Aminudin N. (Institute of Electrical and Electronics Engineers Inc., 2024)
The International Electrotechnical Commission (IEC) has created standards for transformers, which are normally adhered to by the great majority of those that are used in locations all over the world. When it comes to calculating transformer ratings, Malaysia is one of the nations that use the International Electrotechnical Commission's (IEC 60076-72018) for power transformers. Based on the equations in the standard, transformer rating can be affected by changes of the environmental conditions, e.g. ambient temperature. The recent climate change in Malaysia had an influence on the transformer rating that has been mentioned in the IEC standard. This situation is the impetus for conducting this research in the first place. The ambient temperature profile which is based on a few of the world continents' profiles and also specifically the ambient temperature profile in Malaysia are studied and presented by varying ambient temperatures in the IEC Standard mathematical algorithm. The IEC 60076-7 offers recommendations for the specification and loading of power transformers with regard to operating temperature and thermal ageing. This work will focus on the hot spot and top oil temperature of a transformer. The result shows that by changing the ambient temperature by 10 degrees will give effect to the hot spot and top oil temperature and therefore, the ratings of the transformer will also be affected. 2023 IEEE.